В погоне за наследницей: [роман] / Джулия Куин - Куин Джулия (Шарм : коллекция, 2000)
Экземпляры: ф.19 (ретро) / Инвентарный номер: 36401 / Цена: / Сис.шифр: 84(7Сое)-44 / Авт.знак: К 89 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44